EFFECT OF DIETARY SUPPLEMENTATION OF ALOE VERA (Aloe barbadensis) AND TULSI (Ocimum sanctum) POWDER ON GROWTH PERFORMANCE OF BROILER CHICKENS - Kumar, kaushalendra; Kumar, Govinda; Kumar, Sanjay; Singh , Pankaj Kumar; Kumari, Rajni; Kumari, Savita; Jaiswal, Rohit Kumar; Sinha , Ravi Ranjan Kumar; Gupta, Jai Prakash (The Indian Journal of Animal Sciences, 2026)
A feeding trial was conducted to assess the impact of dietary supplementation with Aloe barbadensis (Aloe vera), Ocimum sanctum (Tulsi) powder, and their combination on broiler performance over 35 days. A total of 200-day-old Cobb 400Y broiler chicks were procured, individually weighed, and randomly distributed into four treatment groups (T0–T3) of 50 birds each, with five replicates of 10 birds per group. The diets were iso-nutritive and included: T0 (basal diet, control), T1 (basal diet + 1.5% Aloe vera), T2 (basal diet + 1% Tulsi), and T3 (basal diet + 1.5% Aloe vera + 1% Tulsi). Results demonstrated that broilers in the T3 group (Aloe vera + Tulsi) showed significant (P T2 > T1 > T0. Additionally, retention of dry matter, crude protein, and ether extract was significantly enhanced in supplemented groups, with the highest values in T3. However, calcium and phosphorus retention remained statistically similar across treatments. In summary, combined supplementation of Aloe vera and Tulsi powder effectively improved growth performance, nutrient utilization, and feed efficiency, highlighting its potential as a natural growth promoter in broiler production.